Cosmetics: conceptions of students in High School (Research, Society and Development, 2020)
It is often realized a great difficulty for high school students to understand topics of organic chemistry, which is conceptually complex since it requires to perceive and understand issues that are not connected with the student reality. Thus, the use of substances that are present in daily life, such as cosmetics, can assist in the learning of these students when teaching chemistry. With this in mind, the present work aims to propose to analyze the conceptions of high school students from a public school, on the theme of cosmetics, in addition to promoting a University Extension Project, elaborating together with students, a cosmetic used by people daily. This work has been carried out with groups of 23 second-year and 16 third-year students in a public school in the city of Faxinal do Soturno (RS) with a total number of 39 students with a age interval between 16 to 20 years . Data has been collected with two questionnaires, the first regarding student conceptions regarding cosmetics and perfume industry ad a quiz with selected ENEM past regarding organic chemistry issues. The analysis of the material allowed us to conclude that students have very little knowledge regarfing the chemistry employed in cosmetic and also showing strong difficulties when interpreting ENEM questions regarding organic chemistry. With that, note if the importance of addressing relevant topics in the classroom, such as cosmetics, this topics is the students' daily lives and can help and facilitate the approach to chemistry in the classroom.